Pengentasan Mental Miskin pada Anak-anak Dusun Banyuasin Desa Malingmati dengan Sekolah Alternatif SERA - Thohir, Muhammad Bakhru; Permatasari, Fida Yulia; Hidayati, Nur Rahma Anggun; Andreanto, Dicky; Pambudi, Muhammad Halim; Roziqin, Muhammad Khoirur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Poverty is not only a matter of imbalance in the value of one's income and expenditure, but more than that, poverty is also a mental model problem. Poverty mitigation is not only completed in the economic sector, but also in education, because the education sector plays a vital role in resolving mental model problems. In Indonesia, one of the problems of education is inequality, which is caused by infrastructure and finally results in the ability to organize education optimally. Malingmati is one of the most poverty-stricken villages in Bojonegoro, and Banyuasin is the most inaccessible hamlet. This creates a domino effect of many people who deliberately look poor in order to keep getting donations, and this is a mental model problem, not an economic one. SERA is an alternative school that was initiated to develop children's mindset to be brave enough to aspire and gain access to a wider world. SERA is carried out using social intervention and participatory methods. SERA is implemented with coloring activities, creativity demonstration, storytelling, literacy sharpening, and health education. The results of SERA found that many children who participated in this programme experienced significant improvements in various aspects including self-confidence, aspirations, creativity, critical thinking skills, and public speaking. These advancements effectively contributed to a shift in their mindset, which previously tended to be more self-centered.